Descriptive aspects of wood as an ally in sustainable civil construction: A statistical analysis - Ihlenfeld, Walter; Auler, Matheus Pacheco; Roio, Iolanda Geronimo Del; Fontolan, Beatrice Lorenz; Forte, Alicia Armanini; Gadda, Tatiana Maria Cecy; Guerrieri, Jaime Miranda; Santos, Ana Paula Borges dos; Silva, Caren Melissa Santos da; Vieira, Gabriel Felipe Pryjma Cardeal (Seven Editora, 2024)
With the global trend of using renewable materials and low energy consumption, wood has reappeared in the national construction scene as an ally in sustainable construction. As it is a natural input, it is non-toxic and does not harm the environment, as well as does not oxidize and has good resistance, thus being a safe option for structures and users. Being the result of the growth of a living being, it implies variations in its characteristics depending on the environment in which the trees develop, different physical and mechanical characteristics are added. To understand these characteristics, a descriptive statistical analysis and correlation and regression model are applied with the SPSS© program with the main physical quantities of tree species used as inputs in the national civil construction. From the correlation matrix, the quantity that has the greatest correlation between the variables is the density, so density is considered as the dependent variable for the regression and the others as independent variables, namely: height, diameter, years of cut, dry density, yield strength, modulus of rupture and strength of the fibers. Thus, a multiple linear regression model was created where the values of R² and adjusted R² indicate that the model can explain more than 90% of the phenomenon and that the correlation between the variables is positive. DOI:https://doi.org/10.56238/sevened2023.006-099